PENINGKATAN PRODUKTIVITAS KELOMPOK USAHA PENJAHIT HOME INDUSTRI DI DESA MEDAN KRIO SUNGGAL - Dolok Saribu, Maryati Evivani; Salman, Rudi; Tarigan, Nelson; HArahap, Mukti Hamjah; Panggabean, Deo Demonta; Syah, Dedy Husrizal (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
The home-based tailoring business group in Medan Krio Village, Sunggal District, Deli Serdang Regency faces challenges in productivity and business management due to limited capital, equipment/technology, and insufficient knowledge of management and financial administration. This community service activity aims to improve the productivity and business capacity of partners through the provision of appropriate technology equipment and human resource capacity building. The implementation methods include problem identification, provision of appropriate technology such as overlock sewing machines and heavy-duty sewing machines, as well as training in bookkeeping and business management. The results show a significant increase in production capacity by up to 100%, from 3–4 to 5–6 clothing pieces per day. Furthermore, 70% of participants demonstrated the ability to prepare financial records, and 75% showed an improved understanding of business management. The combination of equipment assistance and training proved effective in empowering the partners. This program has had a positive impact on the partners’ business development and opens opportunities for similar programs in the future. Keywords: appropriate technology, productivity, empowerment